Prenatal screening for Down Syndrome in Australia: costs and benefits of current and novel screening strategies - O'Leary, Peter; Maxwell, S.; Murch, A.; Hendrie, Delia (Wiley-Blackwell Publishing Asia, 2013)
OBJECTIVE: To analyse the cost-effectiveness and performance of noninvasive prenatal testing (NIPT) for high-risk pregnancies following first-trimester screening compared with current practice.METHODS: A decision tree analysis was used to compare the costs and benefits of current practice of first-trimester screening with a testing pathway incorporating NIPT. We applied the model to 32 478 singleton pregnancies screened between January 2005 and December 2006, adding Medicare rebate data as a measure of public health system costs. The analyses reflect the actual uptake of screening and diagnostic testing and pregnancy outcomes in this cohort.RESULTS: The introduction of NIPT would reduce the number of invasive diagnostic procedures and procedure-related fetal losses in high-risk women by 88%. If NIPT was adopted by all women identified as high risk by first-trimester combined screening, up to 7 additional Down syndrome fetuses could be confirmed. The cost per trisomy 21 case confirmed, including NIPT was 9.7% higher ($56 360) than the current prenatal testing strategy ($51 372) at a total cost of $3.91 million compared with $3.57 million over 2 years.CONCLUSION: Based on the uptake of screening and diagnostic testing in a retrospective cohort of first-trimester screening in Western Australia, the implementation of NIPT would reduce the number of invasive diagnostic tests and the number of procedure-related fetal losses and increase the cost by 9.7% over two years. Policy planning and guidelines are urgently required to manage the funding and demand for NIPT services in Australia.